A single-nucleotide mutation within the TBX3 enhancer increased body size in Chinese horses - Xuexue Liu; Yanli Zhang; Wujun Liu; Yefang Li; Jianfei Pan; Yabin Pu; Han Jianlin; Orlando, L.; Yuehui Ma; Lin Jiang (Elsevier, 2022)
Chinese ponies are endemic to the mountainous areas of southwestern China and were first reported in the archaeological record at the Royal Tomb of Zhongshan King, Mancheng, dated to approximately ∼2,100 YBP.1 Previous work has started uncovering the genetic basis of size variation in western ponies and horses, revealing a limited number of loci, including HMGA2,2LCORL/NCAPG,3ZFAT, and LASP1.4,5 Whether the same genetic pathways also drive the small body size of Chinese ponies, which show striking anatomical differences to Shetland ponies,6 remains unclear.2,7 To test this, we combined whole-genome sequences of 187 horses across China. Statistical analyses revealed top association between genetic variation at the T-box transcription factor 3 (TBX3) and the body size. Fine-scale analysis across an extended population of 189 ponies and 574 horses narrowed down the association to one A/G SNP at an enhancer region upstream of the TBX3 (ECA8:20,644,555, p = 2.34e-39). Luciferase assays confirmed the single-nucleotide G mutation upregulating TBX3 expression, and enhancer-knockout mice exhibited shorter limbs than wild-type littermates (p < 0.01). Re-analysis of ancient DNA data showed that the G allele, which is most frequent in modern horses, first occurred some ∼2,300 years ago and rose in frequency since. This supports selection for larger size in Asia from approximately the beginning of the Chinese Empire. Overall, this study characterized the causal regulatory mutation underlying small body size in Chinese ponies and revealed size as one of the main selection targets of past Chinese breeders.